Effect of three porcelain etchants type (HF-APF-PHA) on porcelain- composite shear bond strength - Kermanshah H.; Kharazi Fard MJ; Yesharim H (Tehran University of Medical Sciences, 2005)
Statement of Problem: Porcelain restorations are susceptible to fracture and a common method for repairing is the use of silane and composite on etched porcelain. Although HF is very effective in porcelain etching but has detrimental effects on tissues. Purpose: In this study, the effect of APF and PHA was compared with HF in porcelain etching. Also the role of silane, unfilled resin and dentin bonding in bond strength of composite- porcelain was evaluated. Methods and Materials: In this experimental in-vitro study, one-hundred twenty porcelain square blocks (552 mm) were prepared and bonding surfaces of each sandblasted. Samples were divided into three groups. The first group (n=40) were etched with buffered HF 9.5% (Ultradent) for 1 min., the second group (n=40) were etched with Iranian APF 1.23% (Kimia) for 10 minutes and the third group (n=40) were etched with Iranian PHA 37% (Kimia) for 1 min. Ultradent silane was applied on the surfaces of half of cases in each group. On the surfaces of half of silane-treated samples unfilled resin was applied and dentin bonding was used on the surfaces of the remaining. Samples without silane were treated in a similar manner. Composite cylinder with 4mm diameter and 2 mm height was bonded to porcelain. Specimens were stored in 37°C distilled water for 24 hours and subjected to 500 cycles. Shear bond strength was measured with an Instron machine and type of fracture was evaluated using a stereomicroscope. Results were analyzed using 3 way ANOVA, Kaplan- Maier and Tukey HSD tests. Results: Findings showed that PHA and APF roughened the porcelain surface without creating retentive micro undercuts but HF etches porcelain and creates retentive microundercuts. Ultradent silane had no significant effect on bond strength of porcelain- composite. Unfilled resin with Ultradent silane compared with dentin bonding with the same silane is more effective in bond strength of composite- porcelain. Conclusion: Based on present study, application of Ultradent silane on sandblasted and etched porcelain with PHA or APF cannot be used as an alternative to this silane on sandblasted and etched porcelain with HF.